Самореалізація у контексті часової перспективи у поліцейських з різним рівнем особистісно-професійної здійсненності - Пономаренко, Я. С.; Ponomarenko, Ya. S.; Пономаренко (Посохова) Яна Сергіївна (Перспективи та інновації науки. Серія: Педагогіка, Серія: Психологія, Серія: Медицина. - 2021. - № 5(5). - С. 803-813, 2021)
Презентовано огляд теоретичних напрацювань закордонних та вітчизняних вчених стосовно психологічних особливостей самореалізації особистості у часовій перспективі. Запропоноване авторське визначення поняттю «особистісно-професійна здійсненність» на прикладі професійної групи – поліцейських. Особистісно-професійна здійсненність –це континуум особистісної реалізованості людини в житті та самореалізації в професії, котрі в сукупності розкривають унікальну лінію життєвого шляху особистості. Встановлено, що відсутність зв’язку між особистісною здійсненністю та професійною самореалізацією у поліціантів унеможливлює ефективне виконання службових завдань та не забезпечує якісне використання ресурсів особистості, що свідчить про низький рівень особистісно-професійної здійсненності. Гармонійне поєднання особистісної та професійної складової у єдину унікальну траєкторію розвитку, сприяє всебічному збагаченню психологічних ресурсів поліцейських та взірцевому виконанню покладених на них службових обов’язків, що демонструє високий рівень особистісно-професійної здійсненності.

A review of theoretical developments of foreign and domestic scientists on the psychological characteristics of self-realization of the personality in time is presented. The author's definition of the concept of "personality's - professional fulfillmentity" on the example of a professional group - police officers. Personality's - professional fulfillmentity is a continuum of personal realization of a person in life and self-realization in the profession, which together reveal a unique line of life of the personality. It has been established that the lack of connection between personality's fulfillmentity and professional self-realization in police officers becomes an obstacle to the effective performance of official duties and does not ensure the quality of personal resources, which indicates a low level of personality's - professional fulfillmentity. The harmonious combination of personal and professional component into a overall unique trajectory of development, contributes to the comprehensive enrichment of psychological resources in the policemen and exemplary performance of their duties, which demonstrates a high level of personality's - professional fulfillmentity. The aim of the article is to determine the psychological content of the time perspective of police officers with different levels of personality's - professional fulfillmentity. The sample of the study was formed of 203 police officers who underwent psychodiagnostic testing according to two methods to be divided into groups according to the levels of personality's - professional fulfillmentity. The results of the respondents were obtained by cluster analysis using two methods: "Questionnaire of Personality’s Fulfillmentity" by O.S. Shtepa and "Type and level of professional self-realization" by Ye.A. Gavrylova. According to the principle of k - means, we divided the subjects into three groups. Low level of personality's - professional fulfillmentity was found in 68 police officers (first group); the average level of personality's - professional fulfillmentity was diagnosed in 43 persons, who were excluded from further study; 92 police officers (second group) demonstrated a high level of personality's - professional fulfillmentity. It has been empirically proven that a group of police officers with a low level of personality's - professional fulfillmentity tend to constantly recall past negative experiences in difficult and stressful situations, which causes them to fear making a mistake again or not coping with a difficult situation and the inability to influence them. Police officers, who have a high level of personality's - professional fulfillmentity, believe that they are fully realized in the profession and life, which motivates them to achieve greater success in the profession and strengthens the desire to become more competent, successful and useful for society and the state.

Представлен обзор теоретических наработок зарубежных и отечественных ученых относительно психологических особенностей самореализации личности во временной перспективе. Предложено авторское определение понятию «личностно-профессиональная осуществимость» на примере профессиональной группы – полицейских. Личностно-профессиональная осуществимость – это континуум личностной реализованности человека в жизни и самореализации в профессии, которые в совокупности раскрывают уникальную линию жизненного пути личности. Установлено, что отсутствие связи между личной осуществимостью и профессиональной самореализацией у полицейских делает невозможным эффективное выполнение служебных задач и не обеспечивает качественное использование ресурсов личности, что свидетельствует о низком уровне личностно-профессиональной осуществимости. Гармоничное сочетание личностной и профессиональной составляющей в единую уникальную траекторию развития способствует всестороннему обогащению психологических ресурсов полицейских и исполнению возложенных на них служебных обязанностей, что демонстрирует высокий уровень личностно-профессиональной осуществимости.
Self-realization in the context of time perspective in police officers with different levels of personality'sprofessional fulfillmentity
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Юридична психологія. Legal psychology. Юридическая психология; поліцейські; police officers; полицейские; поліція; police; полиция; особистісно-професійна здійсненність; personal and professional feasibility; личностно-профессиональная осуществимость; самореалізація; self-realization; самореализация; особистісна реалізованість; personal realization; личностная реализованность; службові обов’язки; official duties; служебные обязанности; часова перспектива; temporary prospect; временная перспектива